"Out of tune can be harmful, but it is legally irrelevant…": considerations about music and work in Brazil from the legislative and legal spheres (Orfeu, 2024)
This article presents a documentary analysis of legislative and legal provisions that address the issue of labor relations in the musical field. We begin by examining the Law No. 3.857/1960, which established the Order of Musicians of Brazil and gave this institution both a regulatory function and a role in valuing the work of musicians. The text follows, then, two judgments in the Federal Supreme Court that determined whether and to what extent the 1960 Law would be accepted by the Federal Constitution of 1988. Thus, based on the arguments presented by the STF ministers, we made critical reflections both in relation to the assumptions regarding and the implications of these discursive constructions.
Keywords: Music and Work; Labor Legislation; Judicial Power